Investigation the effect of Graphene on The Morphology, Mechanical and Thermal properties of PLA/PMMA Blends - Paydayesh, Azin; Azar, Ahmad Aref; Arani, Azam Jalali (Ciência e Natura, 2015)
In this work, Poly Lactic Acid/Poly methyl Methacrylate (PLA/PMMA) blends in various compositions prepared and morphology and properties of these blends was investigated. Moreover, the effect of adding different amounts of Graphene Nanoplatelets (GNP) on the morphology of the blends (by SEM), the interaction of nanopalates with polymer phases (by FTIR) and its effect on the mechanical properties and thermal stability of the samples were examined. The results of the study showed that in different amounts of graphene, these plates were preferentially located in the polymer phases dissimilarly and thus, caused the change of the blend morphology. In addition, measuring the mechanical properties by tensile test and results of thermal analysis by TGA indicated the improvement of thermal stability, modulus and mechanical strength and reduction of the elongation at break of graphene containing blends with increasing the loading of GNP. The changing behavior of the mechanical and thermal properties was proportional to the Graphene localization in blend phases.